The relationship between the dental health knowledge and oral hygiene index of the deaf - Nurliyanasari, Lilis; Wardani, Riana; Susilawati, Sri (Padjadjaran Journal of Dentistry, 2009)
Oral hygiene index can be influenced by behaviour factor. Behavior has three domain consist of knowledge, attitude, and practice. Knowledge will change the behaviour of society which next affects to oral hygiene index. The purpose of the research was to know the relationship between the dental health knowledge and oral and dental hygiene index of the deaf. The research was analytic with the cross-sectional method on 63 subjects on 3,4,5 and 6 level class at hearing impaired in Magelang, obtained using the total sampling. Evaluation of dental health knowledge was viewed from the questionnaire. Oral Hygiene Index-Simplified by Green dan Vermillion used to measured oral hygiene index. The research result showed that 65.08%of the deaf on 3,4,5 and 6 level class at hearing impaired in Magelang was in the good category, OHI-S was in the moderate category. Based on Chi-square test there was no significant relationship between the dental health knowledge and oral hygiene index of the deaf at hearing impaired in Magelang.